Features of sorption of lead (II) and cadmium (II) on carbon sorbent of wood nature - Amerkhanova, Sh.K.; Zhaslan, R. K.; Uali, A.S. (KSU publ., 2014)
temperature of 600 ºC was used as a sorbent. Protodyakonov's equations describing influence of all factors the generalized equations (рН, duration of contact of a sorbent with solution, initial concentration of metals’ ions, temperature) on the sorption capacity of sorbent were obtained as a result of studying cadmium (II) and lead (II) ions’ sorption. The analysis of these results allows concluding that sorption of lead (II) and cadmium (II) ions on sorbents occur rather actively. Also the calculation of basic thermodynamic and kinetic parameters of the sorption process was carried out.
Keywords: sorption; sorbent; heavy metals; sorption capacity of a sorbent; sewage treatment